NUTRITIONAL FEATURES OF PREGNANT WOMEN - Ниязова Ольга Андреевна; Жалолов Нозимжон Нодир ўғли (American Journals Publishing, 2024)
Pregnancy is a period when a woman's body undergoes significant physiological changes, which affects her nutrient needs. Proper and balanced nutrition is essential for the normal development of the fetus and maintaining the health of the mother. This article discusses the nutritional features of pregnant women, the importance of essential nutrients for fetal development, dietary features in each trimester of pregnancy, as well as recommendations for foods to eat and avoid. The results of scientific research on this topic are also presented.
Keywords: Pregnancy, nutrition, vitamins, minerals, nutrients, maternal health, fetal development